EFISIENSI PRODUKSI SISTEM USAHATANI PADI PADA LAHAN SAWAH IRIGASI TEKNIS - SAHARA, DEWI; -, IDRIS (SOCA: Jurnal Sosial Ekonomi Pertanian, 2012)
Product efficiency of lowland rice field farming system research had been conducted in technical irrigation on July to November 2005 in Uepai, Konawe district, Southeast Sulawesi province. Purposive sampling was used to choose location based on Agro Ecological Zone (AEZ). This research aimed to know farmer’s rationality in using production factor. Multiple regression linear was used to analysis the factors influencing production and was continued by allocate efficiency test. The result showed that harvest area, pesticide, and labors have positive effect on production factors. Then, to find maximum benefit, farmer needed reduce the use of SP-36 fertilizer. Therefore, to reach both optimum production and advantage need to extend harvest area, addition of pesticide and labor, and to reduce SP-36 fertilizer dosage.
Keywords: Efficiency, Production, Lowland Rice